Different Types of Epilepsy Based on Clinical and Electroencephalographic (EEG) Findings: Experience at Referral Neuroscience Hospital in Bangladesh - Hussain, Mohammad Enayet; Khan, AFM Al Masum; Islam, Md Nahidul; Mian, Md Ferdous; Azam, Md Bakhtiar; Chowdhury, Rajib Nayan (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: A good history and a standard EEG recording help establish most of the epilepsy syndromes. Objective: The objective of this study was to establish different epilepsy syndromes on the basis of history and EEG in the clinically suspected seizure events. Methodology: This cross-sectional study was carried out in the neurophysiology laboratory of National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2013 to December 2015, which included 2549 patients. EEG was obtained through surface scalp electrodes according to international 10/20 system. Patient and their attendants were interviewed using a semi structured questionnaire. The EEG findings, clinical history and in appropriate cases the neuroimaging, CSF and hematological findings were then correlated. Result: Among the 2549 patients most were children (39.8% less than 10 years old) and young adult (30.63% in 11 to 20 years age group). Male patients outnumbered female (63% and 36 % respectively). The overall sensitivity of EEG in yielding abnormal interictal epileptiform discharges was 42%. About 32% of total 2549 patients were diagnosed as localization-related epilepsy (LRE), 5% idiopathic generalized epilepsy (IGE), 1.41% was Epileptic encephalopathy. Conclusion: In conclusion EEG is helpful in classifying the types of seizure, aids in defining the epilepsy syndrome, predicting the outcome and assists in management of patients. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 3-6